Propriedades estruturais, magnéticas e eletroquímicas de ferritas de cobalto e níquel - Romão, Jéssica Cristina de Abreu (2023)
As the burning of fossil fuels is the main source of CO2 emissions, the electrolysis of water in an alkaline environment appears as an alternative for producing hydrogen in order to produce energy. In this process, to accelerate the oxygen evolution reaction, catalysts based on transition metals were produced to analyze the structural, magnetic and electrochemical properties. Nickel and cobalt ferrites were synthesized by the coprecipitation method. In the structural characterization using the x-ray diffraction technique, the formation of pure phases of CoFe2O4 and NiFe2O4 was proven. In Raman spectroscopy, the samples showed six active Raman phonon modes. Photoelectron spectroscopy showed peaks that are probably associated with Co2+ and Ni2+ species, which are tetrahedrally and octahedrally coordinated with oxygen atoms, and the central O 1s levels of both samples present peaks that are probably associated with the presence of oxygen in the surface network. During magnetization, the formation of hysteresis was observed for both samples, which is in accordance with the literature. The electrochemical results showed that the NiFe2O4 sample presents the best performance in terms of decreasing polarization resistances and increasing capacitances.